Climate Change and Mental Health Nexus in National Climate Policy—Gaps and Challenges - Lea Schlatter; Manasi Kumar; Pushpam Kumar (Annals of Global Health)
Background: Climate change is increasingly recognized as a driver of mental health disorders, exacerbating conditions such as anxiety, depression, and post‑traumatic stress. However, climate policies rarely address mental health considerations. Objective: This study investigates the extent to which mental health is incorporated into national climate adaptation policies, specifically Nationally Determined Contributions (NDCs), from countries classified as high or very high risk according to the INFORM index. Methods: We conducted a systematic literature review and policy analysis of NDCs from 38 high‑risk countries. A keyword‑based approach was used to assess the frequency and depth of mental health references in climate policies. Findings: Only 8 of 38 countries explicitly referenced mental health in their NDCs. Most policies prioritized physical health, with little attention given to the psychological impacts of climate‑related disasters. Vulnerable populations, including children, women, and individuals with preexisting mental health conditions, remain largely unaddressed in these national policies. Conclusions: There is a significant gap in the integration of mental health impact and interventional indicators within climate change policies. Greater investment in interdisciplinary research and policy reforms are needed to ensure climate adaptation strategies address both physical and mental health concerns.